Playing games using EEG signals (part II) - Soh, Cheong Seng (2016)
There are nearly 10 percent of the global population that are diagnosed with Attention Deficit Hyperactivity Disorder (ADHD) by the age of 7, which can impair learning performance as well as their social life. [1] For these individuals, sustaining self-control or attention in performing tasks are highly difficult due to their wide and rapidly changing attention span. Currently, there is no effective clinical methods to prevent this condition. However, treatments targeted at reducing the symptoms of ADHD are available such as psychotherapy, medication as well as diet and nutrition. This can be very costly over a long period of time. This Final Year Project focuses on developing a Brain-Computer-Interface (BCI) application, providing a platform for children with such disorder as well as healthy users to train their 4C’s – Concentration, Control, Confidence and Calmness, through neurogaming. With the use of Emotiv EPOC headset and Emotiv Control Panel, the method of extracting and interpreting electrical activities of the brain is utilized, which is known as Electroencephalography (EEG). In this way, cognitive commands can be interpreted and events can be executed. These events can then be mapped to specific key bindings on the computer keyboard which are used as an input to the system. The 3D and 2D multiplayer games, “MindBlown” and “HoverRun” were developed using Unity, a cross-platform game development engine. By using the cognitive commands trained in the Emotiv Control Panel, the players can control specific functions of the ingame characters, competing to win the game. This project allowed BCI to showcase its potential to the public at the Nanyang Technological University (NTU) College of Engineering (COE) Open House in December 2015 as well as NTU Open House in March 2016.